Microorganisms and viruses causing diarrhea in infants and primary school children and their relation with age and sex in Zakho city, Kurdistan Region, Iraq - Mero, Wijdan M.S.; Jameel, Ahmed Y.; Amidy, Kaveen S. Kh. (International Journal of Research in Medical Sciences, 2017)
Background: Diarrheal diseases in children are a major public health concern in developing countries. Diarrheal infection spreads through contaminated food or drinking-water, or from person-to-person as a result of poor hygiene. This study was conducted to investigate the incidence of different microorganisms associated with diarrhea in infants and primary school children and their relation to sex and age in Zakho city, Kurdistan region, Iraq. Methods: During the period from September 2013 to May 2014, 600 diarrheic samples were collected from both sexes and different ages (<2 to 12) years; these samples were subjected to various diagnostic tests in the Microbiology Laboratories/Biology Department/Faculty of Science/University of Zakho. Results: Out of 600/479 were positive for one or more types of microorganisms including 265 (55.32%) males and 214 (44.67%) females. Among the positive 479 samples, the highest rate of prevalence was with both bacteria and parasites (57.33and 57.00%, respectively), followed by viruses (10.33%) and only1.16% with fungi. The most prevalent enteric microorganisms were found to be E. coli (62.5%), followed by E. histolytica (46.19%), G. lamblia (42.10%) and the lowest H. nana (0.87%). The mixed prevalence were documented in 179 (37.36) cases, with the most common correlation between bacteria and parasites in 76 (42.45 %) cases. All ages showed high rates of prevalence with both bacteria and parasites, the highest bacterial cases being among ages >4-8 years (65.38 and 64.07%), while parasites were among >6-10 years (64.67 and 60.11%). High viral prevalence were recorded among ages <2 to 6 years with the peak among <2 years (40.54%). Conclusions: From this study we conclude that about 57% of diarrheal cases were associated with bacteria, parasites, and viruses with E. coli, E. histolytica, G. lamblia and rotavirus as leading microorganisms. The mixed prevalence with two or more microorganisms was documented in 179 (37.36%) out of 479 positive samples and the rate of microbial prevalence was found to be gender and age dependent.